Pharmacogenomics ofMDR1/ABCB1Gene: the Influence on Risk and Clinical Outcome of Haematological Malignancies - Krzysztof Jamroziak; Tadeusz Robak (2004)
AbstractAbstractPharmacogenomics is a rapidly developing field of biomedical research, which investigates phenotypic and pharmacodynamic consequences of the genetic variations among individuals. The multi-drug resistance-1, MDR1 (ABCB1) gene belongs to ATP-binding cassette (ABC) family and encodes for membrane transporter P-glycoprotein (P-gp). A wide array of P-gp substrates comprises toxic xenobiotics and numerous commonly used medications including anti-cancer drugs. Under physiological conditions P-gp protects cells against toxins, whereas in malignant cells P-gp confers multi-drug resistance phenotype. Moreover, characteristic tissue localisation enables P-gp to influence the uptake, tissue distribution and elimination of P-gp transported drugs. A number of recent studies identified variety of single nucleotide polymorphisms (SNPs) in the MDR1 gene and demonstrated significant ethnic differences in their allelic frequency distribution. Furthermore, it was shown that some of these SNPs, especially silent C3435T polymorphism in exon 26, may alter P-gp expression and transport activity. Consequently, it is likely that specific functional MDR1 haplotypes may result with altered exposure to toxins and drugs, thus influencing predisposition to certain diseases as well as efficacy or toxicity of pharmacotherapy. In this paper, we focus on the available data concerning the impact of MDR1 polymorphism on the risk and clinical outcome of haematological malignancies. The structure and function of P-gp as well as results of studies addressing the relevance of MDR1 polymorphism in non-haematological disorders are also briefly discussed.Keywords: MDR1ABCB1P-glycoproteinPolymorphism